Photoprotective activity of geopropolis produced by Melipona subnitida (Apidae, Meliponinae) in the semiarid of the Brazilian Northeast (Research, Society and Development, 2021)
Although geopropolis has been the subject of many chemical and pharmacological studies, there are few studies investigating the photoprotective activity of formulations containing propolis. Thus, we investigated in vivo the photoprotective efficacy of the cream containing geopropolis extract by macroscopic and histological evaluation of the skin of Wistar rats subjected to ultraviolet radiation (UVB). We also evaluated the chemical composition of hydroethanolic extract using the HPLC-DADESI-MS/MS technique, as well as antioxidant activity by the photocolorimetric method of free radical DPPH (2.2-diphenyl-1-picrylhydrazine) and cytotoxic activity by the in vitro MTT quantitative method [brometo de 3- (4.5dimetiltiazol-2-il)-2.5-difeniltetrazolio]. The extract had a varied chemical composition, 29 different phenolic compounds being detected, distributed between phenols and flavonoids, the latter being represented by chalcones, flavones and flavonols. The highest percentages of DPPH inhibition e o baixo valor de IC50 indicaram que o extrato apresentou alta atividade antioxidante. The hydroethanolic extract did not exert cytotoxic effects since high percentages of viability of L929 fibroblasts were observed after incubation for 72 hours at different concentrations of the extract.  On skin submitted to cream application containing of geopropolis extract and the irradiation with UVB did not occur macroscopic and histological lesions. Thus, we concluded that the cream containing of geopropolis extract produced by Melipona subnitida was able to protect the skin from lesions induced by UVB irradiation, thus demonstrating photoprotective effect.